Anne of Green Gables - Montgomery, L. M. (Lucy Maud) 1874-1942.; Parry, Caroline (New York Bantam Books, 1998)
By mistake, Anne, an eleven-year-old orphan, is sent to live with a lonely, middle-aged brother and sister on a farm on Prince Edward Island and proceeds to make an indelible impression on everyone.
Keywords: Friendship -- Juvenile fiction; Country life -- Juvenile fiction; Orphans -- Juvenile fiction; Prince Edward Island -- Juvenile fiction